Note—Simulating a Lognormal Time Series with Prescribed Serial Correlation - Coleman, Denis R.; Saipe, Alan L. (Management Science, 1977)
This note describes a method of simulating a time series of lognormally distributed observations with prescribed mean, variance, and serial correlation as well as pointing out an error in this procedure described in “A Simulating Model for the Evaluation of Fishing Trawler Designs” by Nickerson et al. [Nickerson, T. B., T. G. O'Flaherty, D. W. Rice. 1973. A simulation model for the evaluation of fishing Trawler designs. Management Sci. 20 (4, Part II) 699–707].